2023
DOI: 10.1039/d2nj05263f
|View full text |Cite
|
Sign up to set email alerts
|

Strain sensing multi-stimuli responsive light emitting lanthanide-based tough and stretchable hydrogels with tunable luminescence and fast self-recovery using metal–ligand and hydrophobic interactions

Abstract: Lanthanide-based hydrogels have recently attracted massive interest due to their multipurpose applications like optical sensing, optical image probe, UV OLED, electroluminescent device and biological applications. Here we have developed dual...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In recent decades, photoluminescent (PL) sensors have received increasing attention in various applications. [1][2][3][4] When light is used as an information carrier for a measurement device or sensor, advantages such as noncontact, high penetrability, and fast response allow substantial temporal and spatial resolution. Depending on the physicochemical characteristics of the materials, their photoluminescence can be sensitive to various physical variables.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, photoluminescent (PL) sensors have received increasing attention in various applications. [1][2][3][4] When light is used as an information carrier for a measurement device or sensor, advantages such as noncontact, high penetrability, and fast response allow substantial temporal and spatial resolution. Depending on the physicochemical characteristics of the materials, their photoluminescence can be sensitive to various physical variables.…”
Section: Introductionmentioning
confidence: 99%
“…Through the fine design of terpyridine-based molecules, ion-sensing smart hydrogel materials have been developed. Panda et al reported double physical cross-linked luminescent hydrogels prepared via the copolymerization of acrylamide, methacrylic acid, and 6-(2,2 ′ ;6 ′ ,2 ′′ -terpyridine-4 ′ -acyloxide)-hexyl acrylamide) [13]. By adjusting the molar ratio of terpyridine sensitizers and Eu 3+ /Tb 3+ , the hydrogels exhibited desirable mechanical properties, wide emission spectra, and selfhealing properties.…”
Section: Introductionmentioning
confidence: 99%